Determination of factors contributing to drug abuse using fuzzy analytical hierarchy process (FAHP) / Norpah Mahat ... [et al.] - Mahat, Norpah; Nur, Khairunnisa; Bidin, Jasmani; Syed Abas, Sharifah Fhahriyah; Mohamad Fadzil, Mohamad Najib; Ibrahim, Izleen (Universiti Teknologi MARA, Kedah, 2024)
Abuse of drugs or any dangerous substance is a very worrying global cross-border issue that can destroy the lives of individuals and communities. Drug abuse is also a critical problem in Malaysia, especially in Perlis. Drug abuse among youth is a very real and prevalent issue which involves all races and genders with different financial backgrounds. The Director General of National Anti-Drug Agency (AADK) stated that in 2023, the number of drug addicts in Malaysia has increased by 27% for the first 6 months to 118,820 compared to 93,534 addicts reported in the same period last year. 65% of the total number involved were youth and teenagers. This fact is very worrying because if actions were not taken to curb this problem, eventually, it would continue to worsen and become a critical problem for our country. The aim of this study is to rank the factors of drug abuse particularly in Perlis and to identify the main factors of drug abuse. Fuzzy Analytical Hierarchy Process (FAHP) is used in analysing the data. This method facilitates to rank the factors based on the data collected from five (5) professional AADK staffs. The result of this study found the main factors of drug abuse that are taking drugs for pleasure followed by managing depression or stress, taking drugs as a stimulant, for pain endurance, curiosity, accidental consumption, peer influence and other factors.